Epidemiology of Chronic Pain in Denmark and Sweden. (23rd May 2012) - Harker, Julie; Reid, Kim J.; Bekkering, Geertruida E.; Kellen, Eliane; Bala, Malgorzata M.; Riemsma, Rob; Worthy, Gill; Misso, Kate; Kleijnen, Jos
Abstract : Introduction . Estimates on the epidemiology of chronic pain vary widely throughout Europe. It is unclear whether this variation reflects true differences between populations or methodological factors. Information on the epidemiology of chronic pain can support decision makers in allocating adequate health care resources. Methods . In order to obtain epidemiological data on chronic pain in Denmark and Sweden, we conducted a literature review of epidemiological data primarily on chronic noncancer pain, prioritising studies of highest quality, recency, and validity by conducting a systematic search for relevant studies. Following quality assessment, data were summarised and assigned to the research questions. Results . The prevalence of moderate to severe noncancer pain was estimated at 16% in Denmark and 18% in Sweden. Chronic pain impacts negatively on perceived health status, quality of life and is associated with increased cost. Despite using pain medications, a large proportion of chronic pain sufferers have inadequate pain control. There was a lack of high-quality and low-bias studies with clear inclusion criteria. Conclusions . In both Denmark and Sweden, chronic pain is a common health problem which is potentially undertreated and warrants attention of health care workers, policy makers and researchers. Future research should utilise clear reporting guidelines to assist decision and policy makers, in this important area.